The Importance of Healthcare Services Research - Kaewsombat, Kuttiya; Khunpiluek, Issara; Jarutheekumporn, Thararat; Sutawa, Wannita (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Health services research plays a crucial role in improving the quality of medical and public health services, as well as discovering new and effective treatment methods. This article aims to review and synthesize knowledge about health services research in Thailand between 2017-2024 to develop policy recommendations for enhancing the quality of health services and reducing inequalities in access to care. The study employs a systematic literature review methodology, drawing from PubMed, Scopus, and Google Scholar databases between 2010-2020. The findings reveal that health research is significant in four main areas: 1) discovering and developing medical innovations, 2) improving evidence-based clinical practice guidelines, 3) addressing disparities in access to health services, and 4) developing knowledge on disease prevention and health promotion. Therefore, continuous support for research is a vital mechanism for sustainably developing the country's healthcare system.